2014
DOI: 10.1002/ejic.201402128
|View full text |Cite
|
Sign up to set email alerts
|

3D/3D Hetero‐Interpenetrating Diamondoid Framework and Homo‐Interpenetrating pcu Network by a One‐Pot Reaction

Abstract: Two new metal-organic frameworks (MOFs) with novel architectures, namely, [Co 2 (NDC) 2 (H 2 MDP) 2 ][(Co(NDC)(H 2 -MDP)] (1) and [Co(NDC)(H 2 MDP) 0.5 ] (2) were synthesized through a one-pot reaction. The metal to ligand ratio was found to influence the formation of the two compounds, and their pure phases were successfully obtained only by adjusting the molar ratios of Co/H 2 NDC/H 2 MDP to be 1:1:1 and 2:2:1, respectively [H 2 NDC = 1,4-naphthalenedicarboxylic acid, H 2 MDP = methylenebis(3,5-dimethylpyraz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Lu et al used a flexible H 2 mdp ligand [H 2 mdp = methylenebis(3,5-dimethylpyrazole)] and a H 2 ndc ligand [H 2 ndc = 1,4-naphthalenedicarboxylic acid] as mixed-linkers with Co(NO 3 ) 2 in a mixture of EtOH and H 2 O to prepare the hetero-IPCP 23 of [Co 2 (ndc) 2 (H 2 mdp) 2 ][Co(ndc)(H 2 mdp)], which comprised a 3D + 3D hetero-interpenetrating diamondoid framework. 55 Hetero-IPCP 23 exhibited non-symmetry-related three-fold chiral 3D/3D interpenetration in the chiral space group P 2 1 2 1 2 1 consisting of one dia net with left-handed helical chains and two dia nets with right-handed helical chains. Zheng et al reported the first example for non-symmetry-related two-fold chiral 3D/3D interpenetration with six kinds of helices in the orthorhombic space group P 2 1 2 1 2 1 .…”
Section: Identical Topologies and Identical Compositionsmentioning
confidence: 98%
“…Lu et al used a flexible H 2 mdp ligand [H 2 mdp = methylenebis(3,5-dimethylpyrazole)] and a H 2 ndc ligand [H 2 ndc = 1,4-naphthalenedicarboxylic acid] as mixed-linkers with Co(NO 3 ) 2 in a mixture of EtOH and H 2 O to prepare the hetero-IPCP 23 of [Co 2 (ndc) 2 (H 2 mdp) 2 ][Co(ndc)(H 2 mdp)], which comprised a 3D + 3D hetero-interpenetrating diamondoid framework. 55 Hetero-IPCP 23 exhibited non-symmetry-related three-fold chiral 3D/3D interpenetration in the chiral space group P 2 1 2 1 2 1 consisting of one dia net with left-handed helical chains and two dia nets with right-handed helical chains. Zheng et al reported the first example for non-symmetry-related two-fold chiral 3D/3D interpenetration with six kinds of helices in the orthorhombic space group P 2 1 2 1 2 1 .…”
Section: Identical Topologies and Identical Compositionsmentioning
confidence: 98%
“…Aromatic carboxylic acids are important starting materials for the synthesis of metal–organic frameworks (MOFs) and metal–organic coordination complexes and for use in crystal engineering. , The variety of positions of the dicarboxylic acids that are available, often commercially, makes this kind of molecule an ideal synthetic building block. Substituted naphthalenes also have importance as model compounds for asphaltene, the heavy component of crude oil …”
Section: Introductionmentioning
confidence: 99%